A study investigating short- and medium-term effects on function, bone mineral density and lean tissue mass post-total knee replacement in a Caucasian female post-menopausal population: implications for hip fracture risk. Issue 8 (August 2016) - Hopkins, S.; Toms, A.; Brown, M.; Welsman, J.; Ukoumunne, O.; Knapp, K.
Abstract Summary Significant increased hip fracture incidence has been reported in the year following total knee replacement. This study demonstrates that bone and muscle loss is a post-surgical consequence of total knee replacement, alongside poor outcomes in function and activity potentially contributing to reduced quality of life and increased hip fracture risk. Introduction A significant increase in hip fracture incidence in the year following total knee replacement (TKR) surgery has been reported. This study investigated function and activity following TKR and the effects of limited mobility on bone and muscle loss and their potential contribution to hip fracture risk. Methods Changes in dual-energy X-ray absorptiometry (DXA) (GE Lunar Prodigy, Bedford MA), bone mineral density (BMD) at the neck of femur (NOF), total hip region (TH) and lumbar spine were measured alongside leg lean tissue mass (LLTM) in post-menopausal Caucasian females following TKR (N  = 19) compared to controls (N  = 43). Lumbar spine trabecular bone scores (TBSs) were calculated. Ipsilateral/contralateral weight bearing, lower limb function, 3-day pedometer readings, pain levels and falls were also recorded. Measurements were obtained at pre-surgery baseline and at 6 weeks, 6 months and 12 months post-surgery. Results No statistically significant differences were demonstrated between groups at baseline bilaterally in LLTM or BMD at the NOF and TH. Losses in ipsilateral NOF and TH BMD and contralateral LLTM were significantly higher in the TKR group at 6 months. Impairment in function and weight bearing persisted in the TKR group 12 months post-operatively alongside deficits in bilateral muscle mass and ipsilateral NOF and TH BMD. Falls incidence was not significantly higher in the TKR group. Conclusions Bone loss at the hip with associated muscle loss is a consequence of TKR that, in addition to poor patient outcomes in function and activity, potentially contributes to increased hip fracture risk in the year following surgery.